Factors behind People Opting for a Smart Band/Watch and Fitness being a Major Component - Suyash Gaikwar (International Journal of Advanced Science and Technology, 2020)
Aging population has become a global phenomenon. It is also empirical that the current generation will not return to the lifestyle and young population that our ancestors knew. It is there very important that we use any means possible to improve the quality of life our people including sensing and health technology. Smartwatches and bands are devices that can provide health information and easy accessibility. Through this paper, we would investigate the awareness of smartwatches among people and how much does fitness factor affect the wearing behaviour. Majority of today’s population is focused on their health and try to stay fit and measure their success. The study revealed the same result, which is people have started buying smart bands and watches which serves as a time keeper as well as a measure for their fitness.